Experimental and Numerical Investigation of Solar Airflow Windows - Friedrich, Kelton E. (My University, 2011)
Solar thermosiphons integrated into the thermal envelop of buildings has been studied for their potential to take advantage of solar energy in heating buildings. The annual performance of solar thermosiphons cannot currently be predicted with the correlations from previous research. Also, no work has been done on the supply mode of a solar thermosiphon even though it has the potential to provide heating and fresh ventilation air. An investigation was done with the goal of developing a numerical model that could predict the performance of the supply mode of a solar thermosiphon. The numerical model included infrared thermal radiation and conduction through the glass, phenomenon which had not been used in previous numerical models. To validate the numerical model a novel steady state experiment was developed. This experiment included radiation as the heat source and the ability to vary geometric lengths. The performance parameters of mass flow rate and thermal efficiency were comparable between the numerical predictions and experimental results. However, due to uncertainties in the current experimental setup, full validation of the numerical model was not possible. These uncertainties would have to be addressed before the numerical model that was developed can be fully validated and used for generating correlations. After consideration of practical implementation constrains, it was shown that it was easier to implement the indoor air curtain mode of a solar thermosiphon than the supply mode. The indoor air curtain mode provides the same amount of energy from solar radiation to heat a building as the supply mode of a solar thermosiphon.
Keywords: Solar thermosiphon; Natural convection; Trombe Wall; Solar chimney; Experiment; Numerical; Energy Systems; Energy Systems